2019
DOI: 10.3390/w11050906
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Greenhouse Gas Emissions in Centralized and Decentralized Water Reclamation with Resource Recovery Strategies in Leh Town, Ladakh, India, and Potential for Their Reduction in Context of the Water–Energy–Food Nexus

Abstract: With the constant increase of population and urbanization worldwide, stress on water, energy, and food resources is growing. Climate change constitutes a source of vulnerability, raising the importance of implementing actions to mitigate it. Within this, the water and wastewater sector represents an important source of greenhouse gas (GHG) emissions, during both the construction and operation phase. The scope of this study is to analyze the GHG emissions from the current and future water supply scheme, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Lahmouri et al [7] analysed greenhouse gas (GHG) emissions and compared possible water reclamation with resource recovery scenarios in the town of Leh in India: a centralised scheme, a partly centralised combined with a decentralised scheme, and a household-level approach. Potential sources of reduction of GHG emissions through sludge and biogas utilisation have been identified and quantified to seize their ability to mitigate the carbon footprint of the water and wastewater sector.…”
Section: Integrated Assessment Methodsmentioning
confidence: 99%
“…Lahmouri et al [7] analysed greenhouse gas (GHG) emissions and compared possible water reclamation with resource recovery scenarios in the town of Leh in India: a centralised scheme, a partly centralised combined with a decentralised scheme, and a household-level approach. Potential sources of reduction of GHG emissions through sludge and biogas utilisation have been identified and quantified to seize their ability to mitigate the carbon footprint of the water and wastewater sector.…”
Section: Integrated Assessment Methodsmentioning
confidence: 99%
“…Both types explore the potential impacts of innovative techniques or technologies. Exceptions examined the potential of decentralized governance (Lahmouri et al 2019), household investment strategies (Topi et al 2016), or urban planning (Gondhalekar and Ramsauer 2017). Nearly all studies recommended more research before implementation, often citing the need for a better understanding of how the suggested change would interact with society.…”
Section: Proposed Solutionsmentioning
confidence: 99%
“…In Beijing, China, Li et al (2019a, b) identified a hierarchy of critical FWE systems and subsystems, and Elagib et al (2019) advocated integrated decision-making with respect to hazard management and the FWE nexus in Khartoum, Sudan. Finally, Lahmouri et al (2019) showed the benefits of the decentralized management of FWE resources, emphasizing the need for decision-making among local people who are best-informed about the situation.…”
Section: Policy Relevancementioning
confidence: 99%
“…Reviewing existing studies linking the EWF and climate change, Lahmouri, et al [23] expressed concern about the polluting atmospheric function of climate change on EWF resources caused by the strong pressure of economic development. Moreover, Maji, et al [24] examined renewable energy use in economic development and climate change resilience in Western Africa.…”
Section: Literature Reviewmentioning
confidence: 99%